The Dataset of the Geographical Dispersal of Islamic Cream Ware in Southern Bilad Al-Sham (8th to 11th Centuries) - Piotr Makowski; Julia M. Chyla (Journal of Open Archaeology Data, 2024)
This dataset constitutes a comprehensive inventory of 125 excavated sites from the territory of southern Bilad al-Sham attesting the occurrence of the Islamic Cream Ware (ICW). It provides information on the typological variety, dating, and general contexts of appearance of this pottery class. In addition, it is supplemented by bibliographical references to all sites included in the database. In general, the following dataset can appear useful for scholars working on the various subjects related to Early and Middle Islamic pottery and settlement of southern Bilad al-Sham.